PRONATEC - um “novo” modelo de qualificação profissional? Um estudo da organização pedagógica do Pronatec Concomitante do Estado do Paraná - Anjos, Sulanita Nunes Horta dos (2016)
Professional education as a policy of labor training for the job market has been configured, historically, for actions and programs disjointed of education regularly systematized in the country.In this sense we understand that in the past governments, accentuated the public disservice when promoting educational pseudo proposals that usurp the working class the possibility of a professional educational background that includes a consistent basic education linked to high school and professional curriculum space. The main objective that motivated the present study was to know a professional education policy that is linked to the regular high school, as the possibility of professionalization. Thus, the proposal of this research is to discuss the aspects of pedagogical organization of the National Program for Access to Technical Education and Employment, known as Pronatec, in the concomitant modality, in the offered units of Paraná state. First, it realizes a brief overview of professional education history in Brazil, which occurs in this modality of education from the needs of understanding the economic sector in the country, mainly in skilled labor preparation.Following, it was necessary to understand the process of professional education running throughout the professional education history, if driven to propaedeutic teaching or directed to the labor formation, also oriented to the rearticulation and the equivalence in the high school with technical education, supporting the expansion of professional formation through private entities. The central question of this dissertation is circumscribed on technicist influence of the pedagogical model adopted by Concomitant Pronatec, which is characterized by privileging labor training that promotes the economic development of the country, centered on priority attention to the labor market and less on emancipatory educational training of workers.